Global branding breakthroughs in research and practice (Business Science Reference, 2020)
"This book provides international insights into marketing strategies and techniques employed to create and sustain a globally recognized brand. It highlights a range of pertinent topics such as brand communication, consumer engagement, and product innovation"--